A case of cerebral infarction due to aplastic or twig-like middle cerebral artery after lung cancer surgery. Issue 9 (20th September 2022) - Hato, Tai; Yamaguchi, Masatoshi; Sugiyama, Ato; Aoki, Kohei; Fukuda, Hiroki; Kohno, Mitsutomo; Nakayama, Mitsuo
Abstract: Aplastic/twig-like middle cerebral artery is a rare vascular abnormality. We report a case of postoperative cerebral infarction caused by this disease. The patient is a male in his 40s. A 9-cm tumour was revealed to have invaded the superior vena cava from his right lung. He underwent right upper and middle bilobectomy. Due to the vascular invasion, the intraoperative bleeding exceeded 2 litres. Mechanical ventilation was required for postoperative pneumonia. After extubation, he was unable to write and was found to have cerebral infiltration in the left middle cerebral artery region. The cause of the cerebral infarction was investigated, but no thrombus in the left atrium or arteriosclerosis was found. No atrial fibrillation was observed during or after the surgery. Magnetic resonance angiography of the brain revealed an aplastic/twig-like middle cerebral artery.